Price markups and upstreamness in world input-output data - Colonescu, Constantin (My University, 2021)
This research uses the publicly available World Input-Output Database (WIOD) to investigate the relationship between an industry’s markup and its upstreamness, the industry’s position in the vertical chain of production; the research also identifies common attributes among highmarkup industrial sectors: higher-markup industries display a higher level of capital compensation and a lower share of labour and other inputs in the value of output. Finally, it is found that upstream industries, those producing mostly raw materials and intermediate products enjoy higher market power than their downstream counterparts. This result could be among the first in the literature to find evidence of double marginalization at an industry level of aggregation. It also suggests that virtually all final product prices may incorporate substantial markups through their inputs.
Keywords: world input-output table; price markup; upstreamness